Physical and Biochemical Characteristics of Eco-Enzyme Solutions as Biology Learning Resources for Senior High Schools - Fadhillah Marta; Ratna Dewi Eskundari (Jurnal Biologi Tropis, 2026)
The Merdeka Curriculum emphasizes student-centered and experiment-based learning that utilizes the surrounding environment as a contextual learning resource. This study analyzes the physical characteristics (pH, color, and odor) and biochemical properties (primary and secondary metabolites) of ecoenzyme solutions made from molasses and palm sugar. This study utilized an experimental approach and generated quantitative descriptive data to identify differences in physical and biochemical characteristics between the two solutions. The results show variations in pH, odor intensity, color, and metabolite content, indicating that the type of raw material influences the properties of the ecoenzyme. These findings can be used as contextual learning resources for senior high school and vocational health students in biology and chemistry learning under the Merdeka Curriculum. In addition, the analysis of primary metabolites (reducing sugars, proteins, organic acids, and lipids) and secondary metabolites (alkaloids, saponins, tannins, flavonoids, and coumarins) provides meaningful scientific evidence that links fermentation processes with observable chemical changes. This integration of laboratory investigation and real-life environmental materials supports the development of students’ scientific literacy, critical thinking, and experimental skills through contextual and inquiry-based learning activities.